USING TELEGRAM TO IMPROVE ENGLISH PRONUNCIATION OF HIGH SCHOOL STUDENTS - Sudarmaji, Imam; Izza Maulida, Siti (TELL - US JOURNAL, 2023)
This study investigated the use of social networking site Telegram in improving students’ pronunciation of eleventh grade students in one of senior high school in Tangerang, Indonesia. A total of 24 students were taken as the sample in the current study. Non-randomized one class pretest-posttest design was used in the study. Using quasi experimental research one-class pretest-posttest design, the students in the experimental class completed the process through Telegram. The tests and questionnaires were used to collect the data. In order to test whether there was an improvement within the class, the hypothesis was tested using the t-test and obtaining the gain scores. The result showed that the pronunciation of students was improved. They were interested in learning through the media, wanted to learn new things, and active throughout the learning process. Based on the percentages, students’ posttest showed that the pronunciation of students was improved after using social networking site Telegram. Moreover, this research also found that the evaluation of learning model was good, the students’ learning motivation was very good, and made a good class atmosphere in the experimental class throughout the learning process by using social networking site Telegram.